TINGKAT PENDIDIKAN, UPAH, INFLASI, DAN PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN DI INDONESIA - Indra Suhendra; Bayu Hadi Wicaksono (Jurnal Ekonomi-Qu, 2020)
The aim of this study is to determine the influence of education level, wages, inflation, and economic growth to unemployment rate in Indonesia during the Period of 2010 to 2012. Panel data regression analysis model is conducted as the research model. The research results shows that during 2010 to 2012, educations level in bachelor degree (TPS1), wages, inflation and economic growth have significant effect to unemployment rate, whereas education level in senior high school (TPSMA) has not significant influence to unemployment rate. Simultaneously the independent variables have significant influence to the dependent variable. The coefficient of determination (R2) shows 0.722353, meaning that the variasion of dependent variable can be explained by the variasion of independent variables as many as 72.2353 percent .